2018
DOI: 10.4317/jced.54688
|View full text |Cite
|
Sign up to set email alerts
|

Porosity analysis of MTA and Biodentine cements for use in endodontics by using micro–computed tomography

Abstract: BackgroundThe purpose of this study is to compare the porosity of two repair cements, White ProRoot® MTA and Biodentine®. These samples were analyzed by using micro-computed microtomography.Material and MethodsSixteen samples were used in the study that were divided according to the composition of the materials used. White ProRoot® MTA (n = 8) and Biodentine® (n = 8) were the samples prepared according to the manufacturer’s instructions. They were placed in silicone molds of 5 ± 0.1mm in height and an internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
8
1
6
Order By: Relevance
“…Basturk et al and Aminoshariae et al concluded that ultrasonication caused more voids than hand condensation and suggested that MTA might not be ideal for ultrasonic activation because of its powder-to-liquid ratios (23,27). In addition, Guerrero et al reported that Biodentine had less porosity than ProRoot WMTA (28). The aforementioned studies were carried out by placing the materials in standardised moulds.…”
Section: Discussionmentioning
confidence: 99%
“…Basturk et al and Aminoshariae et al concluded that ultrasonication caused more voids than hand condensation and suggested that MTA might not be ideal for ultrasonic activation because of its powder-to-liquid ratios (23,27). In addition, Guerrero et al reported that Biodentine had less porosity than ProRoot WMTA (28). The aforementioned studies were carried out by placing the materials in standardised moulds.…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio, los resultados son similares a los obtenidos por Guerrero et al (2018), pues ambos estudios dan como resultado un mayor número de poros en el MTA ( 1 ).…”
Section: Discussionunclassified
“…The roots were divided into five groups: MTA, C, C + chitosan (Cchi), C + zirconium oxide (Czio), C + hydroxyapatite (Chap), as well as two subgroups: (A) without phosphate buffer solution (PBS) and (B) with PBS. The sample size ( n = 10 for each subgroup of each assessment, that is, apatite‐like forming ability, pH and Ca 2+ release, bond strength and porosity) was determined according to previous studies (Do Carmo et al, 2018; Guerrero & Berástegui, 2018; Marques et al, 2015; Oliveira, Andrade, Parreira, Jacobovitz, & Pandolfelli, 2015; Parreira et al, 2016; Sisli & Ozbas, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The porosity after final setting of the cement represents one of the major limitations of endodontic cements (Basturk, Nekoofar, Gunday, & Dummer, 2014; De‐Deus et al, 2015; Parirokh & Torabinejad, 2010). In fact, porosities may increase the risk of penetration of contaminated body fluids and blood, which makes the material unstable and results in contamination of the root canal system (Camilleri et al, 2014; Guerrero & Berástegui, 2018; Sisli & Ozbas, 2017). Therefore, the cement apatite‐like forming and sealing abilities are essential for the success of retrograde endodontic treatment (Camilleri et al, 2014; Parirokh & Torabinejad, 2010).…”
Section: Introductionmentioning
confidence: 99%